Teachers’ Challenges in Teaching Online English to Young Learners: A Case Study in Pandemic Era - Fahriany, Fahriany; Fitriani, Fitriani; Farhan, Lulu; Husna, Nida; Hidayat, Didin Nuruddin; Mahlil, Mahlil (Jurnal Basicedu, 2022)
This study aims to explore the challenges of primary school teachers in teaching online English to young learners in the pandemic era and teachers’ views toward teaching online English. The teachers also provide the solutions to overcome the problems. This is a qualitative research that employs a case study as the approach. The data are obtained through questionnaires and semi-structured interviews with 20 English teachers of primary schools. The results show many challenges emerged from three sides: instructional activity, time management, and student assessment. Challenges of instructional activity cover students’ motivation, English levels of student proficiency, communication, cooperative learning, and teaching writing. Time management challenges include having a limited amount of time and providing feedback. Meanwhile, student assessments assess students’ attitudes and cognitive skills. This study suggests the administrators and authorities of education policymakers evaluate the guidelines to enhance the quality of online teaching, especially for elementary schools.